2009
DOI: 10.1159/000180265
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormones and Modulation of Immunity against Leishmaniasis

Abstract: Sex-associated hormones such as estradiol, testosterone and progesterone have all been shown to modulate immune responses, which can result in differential disease outcomes between males and females, as well as between pregnant and nonpregnant females. Most parasitic diseases, including leishmaniasis, usually result in more severe disease in males compared with females. This review highlights our current knowledge concerning the role of sex hormones in modulating leishmaniasis in both clinical settings and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 110 publications
4
70
0
3
Order By: Relevance
“…Indeed, gonadectomy and hormone therapy in mice suggest that estrogens are particularly associated with the ability of females but not males to produce IFNγ and a Th1 immune response (Roberts et al, 2001). Sex-differences in susceptibility to infection have also been observed for other parasites such as Plasmodium (Klein et al, 2008;Snider et al, 2009). We further found that protection against L. mexicana was gender-specific, with female hamsters being significantly protected by the DNA vaccine, while males failed to show protection.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Indeed, gonadectomy and hormone therapy in mice suggest that estrogens are particularly associated with the ability of females but not males to produce IFNγ and a Th1 immune response (Roberts et al, 2001). Sex-differences in susceptibility to infection have also been observed for other parasites such as Plasmodium (Klein et al, 2008;Snider et al, 2009). We further found that protection against L. mexicana was gender-specific, with female hamsters being significantly protected by the DNA vaccine, while males failed to show protection.…”
supporting
confidence: 55%
“…Pregnancy (Osorio et al, 2008) and lactation (GomezOchoa et al, 2003) have both been found to reduce susceptibility to Leishmania infection in female hamsters. Gender differences in the incidence of visceral leishmaniasis has also been reported in human and dog populations, with males being usually more susceptible (Roberts et al, 2001;Snider et al, 2009). Sexual hormones are thought to contribute to the difference in cytokine production (Ahmadi & McCruden, 2006;Lezama-Davila et al, 2007;Roberts et al, 2001;Travi et al, 2002).…”
mentioning
confidence: 99%
“…However we do not consider this finding to be conclusive regarding the possible role of sex as demonstrated in the mouse model 33 . More studies will be done regarding the role of sex in susceptibility and/or resistance to the infection by L. (L.) mexicana in P. yucatanicus.…”
Section: This Is the First Study That Examines P Yucatanicus Clinicamentioning
confidence: 61%
“…In particular, steroid hormones have been implicated as crucial contributors to the immune response either as enhancers, as is the situation with estrogens, or as endogenous inhibitors, as is the case with testosterone and glucocorticoids (22,23). This is best exemplified by the much higher incidence of autoimmune diseases such as multiple sclerosis in women, where the female to male ratio is significantly higher (2:1 to 3:1) (24,25).…”
mentioning
confidence: 99%